The Military's Institutional Teleology: Defending the Common Good - Ford, Shannon (2016)
This paper examines the teleology of the military as a social institution. That is, the institutional purpose or ends for which it exists. First, I consider differing views for the institutional teleology of the military as a state-sanctioned social institution. I demonstrate that the modern military is more than an instrument for doing harm or fighting wars. I also examine the conventional approach that says teleology of the military is to carry out the State’s responsibility for defending the “life” of a political community from external threats. Then I examine cosmopolitan criticisms of this view, which argue that the moral purpose of the military should be to preserve a just peace and protect human rights. I conclude that the morally responsible State uses its military to defend the common good. In particular, I argue that a state’s military should defend the common good of the political community it serves, which includes, but is not limited to, fighting wars against external aggression. I also argue, however, that a state has important moral responsibilities to the common good outside the interests of its own narrowly defined political community. Importantly, it has a moral obligation, albeit weakened, to use military force to protect the lives of outsiders.